Функціональний стан ЦНС та ВНД за умов комбінованого радіаційно-хімічного впливу - Севериновська, О.В.; Зайченко, О.Ю.; Рибальченко, В.К.; Пахомов, О.Є. (Видавничий дім "Академперіодика" НАН України, 2007)
It has been found that strengthening the absolute spectral capacity in α- and β-ranges in cortex and subcortical structures of brain under the combined chronic influence of radiation-chemical factors testifies to the activation of nervous processes in CNS, and their regulation is complicated in connection with disturbances of ionic transport and pro/antioxidation homeostasis in nervous cells.